Kolaborasi TPS-Digidic pada Pembelajaran Teks Naratif dalam Pemenuhan Mutu Pembelajaran Aspek Literasi - Zaimatun Zaimatun (Jurnal Didaktika Pendidikan Dasar, 2023)
National Assessment policy that consists of Minimum Competency Assessment, character survey, and learning environment survey is to know the real education quality. Its result is hoped as a feedback for an instance i.e. school to manage better learning. The aim of TPS-digidic collaboration in narrative learning is to show its effectiveness in learning quality fulfilling of literacy aspect. TPS is an acronym of Three Paragraphs Short story. While, digidic is an acronym of digital dictionary. This research uses experimental research focused on pre-experimental design especially on intact-group comparison. The result shows that TPS-digidic collaboration in narrative learning can increase IXA’s competency to do the tess equal on Minimum Competency Assessment of literacy aspect. Its increase is 26.68%. The percentage of minimum competence criteria is also increase 13,63%. While the learning activeness increases about 20,81%. TPS-digidic collaboration in narrative learning is effective to create learning quality fulfilling of literacy aspect.